Primary ciliary dyskinesia diagnosed on nasal mucosal biopsy in two newborns. Issue 2 (April 2014) - Yasuhara, Jun; Yamada, Yuji; Hara, Kaori; Suhara, Rieko; Hattori, Yujiro; Yamaguchi, Tetsuji; Mizuno, Yusuke; Kizu, Rika; Bamba, Masahiro
Abstract Primary ciliary dyskinesia (PCD) is a genetic disease that causes abnormalities in ciliary structure and/or function. Ciliated cells line the upper and lower respiratory tracts and the Eustachian tube. Impairment of mucus clearance at these sites leads to sinusitis, repeated pulmonary infections, bronchiectasis, and chronic otitis media. Situs inversus occurs randomly in approximately 50% of subjects with PCD. The triad of situs inversus, bronchiectasis and sinusitis is known as Kartagener syndrome. PCD is usually an autosomal recessive disease, but occasional instances of X‐linked transmission have been reported. Specific diagnosis requires examination of ciliary function or structure on light and electron microscopy. Early diagnosis and respiratory management are important in order to prevent the development of bronchiectasis and deterioration in lung function. We report early diagnosis of PCD on nasal mucosal biopsy in two newborns who presented with prolonged respiratory distress and rhinorrhea.